Biocontrol of Plant Diseases: Antagonist Microorganisms, Biostimulants, Induced Resistance (IR) - Agustí-Brisach, Carlos; Llorens, Eugenio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Biocontrol of plant diseases is considered one of the most important and current challenges of our society due to the need to look for eco-friendly alternatives to chemicals. Thus, research towards the biological control sensu lato [antagonist microorganisms, biostimulants, Induced Resistance (IR)] of plant diseases is an urgent demand for the agro-food sector of the Euroregion as well as for our society in the frame of the European Green Deal. Exploring different biocontrol tools as well as their combined effect against plant diseases is essential to generate knowledge on such topics to look for optimum management strategies in crop protection in the frame of organic and sustainable agriculture. Within this framework, this Special Issue of Plants brings together a collection of research papers on applied plant pathology and targeted reviews of biocontrol, including studies on antagonist microorganisms, biostimulants, and host resistance-inducers against plant diseases.